PENGARUH AUDIT FEE, GOING CONCERN, FINANCIAL DISTRESS, UKURAN PERUSAHAAN, PERGANTIAN MANAJEMEN PADA PERGANTIAN AUDITOR - Bayu Pradhana, Made Aditya; Dharma Suputra, I.D.G. (E-Jurnal Akuntansi, 2015)
Substitution auditor is a behavior that is done by the company to switch auditors. The research objective was to determine the effect of audit fees, going concern opinion, financial distress, company size and management changes at the turn of the auditor. This type of data is in the form of quantitative audited financial statements 2008-2013 period manufacturing companies listed in Indonesia Stock Exchange. Method of sampling is using purposive sampling, the number of samples 96 companies. Data analysis techniques are logistic regression analysis (logistic regression), because the dependent variable using dummy variables. The results of this study are audit fees, going concern opinion and influence management changes at the turn of the auditor. While financial distress and client company size has no effect on the change of auditors.
Keywords: Audit Fee, Going Concern Opinion, Financial Distress, Company Size, Change of Management